Behavioural plasticity induced by intraspecific competition in host orientation in a parasitoid - Martinez, Gustavo Agustin (2017)
1. Accurate measurement of external conditions is fundamental for survival. For parasitoids, in particular, sensing the environmental conditions is key because they are short-lived animals that must acquire information shortly after emergence. 2. This study investigated whether conspecifics during larval growth can influence and modify the decision to orient to different quality hosts in a parasitoid with an active host-seeking larva. How the density of conspecifics during growth modifies these decisions was also studied. 3. When larvae were submitted to increases in the intensity of pre-parasitism competition and then offered different host odours, they increased the orientation to poor-quality hosts likewise. It was also found that this behaviour is general to orientation to hosts in different physiological states. 4. These results show that pre-parasitism competition can influence and modulate orientation to poor-quality hosts when high-quality hosts are not available.